A Compact Fiber Optic Fabry–Perot Sensor for Simultaneous Measurement of Acoustic and Temperature - Xiaoying Liu; Junfeng Jiang; Shuang Wang; Kun Liu; Lei Xue; Xue Wang; Zhe Ma; Xuezhi Zhang; Yongning Zhang; Tiegen Liu (IEEE Photonics Journal)
A compact fiber optic Fabry-Perot (F-P) sensor for simultaneous acoustic and temperature measurement has been proposed in the research. The sensor consists of silicon-glass-silicon sandwich structure by anodic bonding. The air F-P cavity with a circular hole and slots utilizes the deformation of the silicon membrane to realize acoustic measurement, and the silicon F-P cavity utilizes the temperature sensitivity of the refractive index of silicon to realize temperature measurement. The acoustic signal and temperature information could be recovered by acoustic and temperature demodulation method, respectively. The experimental results demonstrate that the sensor has a signal-to-noise ratio (SNR) of 53 dB and the acoustic sensitivity of 4.65 mV/Pa at 21 kHz, and the temperature sensitivity of 123.10 nm/°C at 20 °C∼120 °C. The proposed fiber optic F-P sensor has great potential for simultaneous acoustic and temperature measurement in aviation, due to its compact structure, mass production and immunity to electromagnetic interference.